Sumber Historis Pancasila sebagai Sumber Sosiologis Pancasila - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Mafazatul Iqamah; Rizya Oktavia; Zaskia Putri Satya Ningrum (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Pancasila, as the foundation of Indonesia, has a historical source that includes the historical background and thoughts of the founding fathers. This can be seen from the ratification of the Pancasila on August 18, 1945 and Soekarno's speech on June 1, 1945 formulating the basic values of the state. historical source Pancasila reflects Indonesia's socio-cultural diversity, including values such as gotong royong, tolerance, and deliberation, which form the basis of unity amid ethnic differences. Both complement each other in shaping the nation's identity and ideology.